The short-term impact of COVID-19 on Ethiopia’s economy through external sector channels: An economywide multiplier model analysis - Aragie, Emerta A.; Taffesse, Alemayehu Seyoum; Tamru, Seneshaw (International Food Policy Research Institute, 2020)
The COVID-19 pandemic is expected to considerably affect the Ethiopian economy directly and indirectly due to global shocks and to the different restrictive preventative measures the country is taking. We analyze these economic effects using multisector economywide income multiplier models built on the two latest Social Accounting Matrices (SAMs) developed for Ethiopia. Three external sector channels are the focus of the analysis: commodity exports, strategic imports, and remittances. Results indicate that in the absence of any policy responses, the Ethiopian economy is expected to experience a loss of approximately 4.3 to 5.5 percent of its annual GDP due to exports, strategic imports, and remittances that are one-third lower relative to the no-COVID situation over a period of six-months. This translates into estimated reductions in labor income of between 4.2 and 5.2 percent. The SAM multiplier model estimates also imply that these negative shocks lead to household income losses that amount to between 3.9 and 6.4 percent. In particular, the urban poor will be the most affected as they lose real incomes in the range of 6.6 to 8.5 percent. These income losses are estimated to result in a 3.5 percentage point rise in the national poverty headcount.